2015
DOI: 10.1016/j.sjbs.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Thuja orientalis extracts against watermelon mosaic virus (WMV) on Citrullus lanatus

Abstract: Watermelon mosaic potyvirus (WMV) is considered as an important virus infecting watermelon and causing adverse effects on crop productivity. To overcome this problem one of the main objectives of plant breeders is to make these strains less effective in the ability to infect plants by treatment with plant extracts. Due to the advantages of plant tissue culture, in vitro, in the process of the selection of different cultivars under biotic stress, this study was conducted to achieve this aim by evaluating the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Reports of the antiviral activities of plant crude extracts and their constituents against plant viral infection have increased during the last decade [ 32 ]. Many plant extracts of Boerhaavia diffusa , Clerodendrum aculeatum , Mirabilis jalapa , Potentilla arguta , Sambucus racemosa , and Thuja orientalis exhibit inhibitory effects against plant viruses [ 33 , 34 , 35 , 36 , 37 ]. Additionally, several virus-inhibiting compounds, including flavonoids, triterpenoids, alkaloids, and proteins, have been isolated from higher plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the antiviral activities of plant crude extracts and their constituents against plant viral infection have increased during the last decade [ 32 ]. Many plant extracts of Boerhaavia diffusa , Clerodendrum aculeatum , Mirabilis jalapa , Potentilla arguta , Sambucus racemosa , and Thuja orientalis exhibit inhibitory effects against plant viruses [ 33 , 34 , 35 , 36 , 37 ]. Additionally, several virus-inhibiting compounds, including flavonoids, triterpenoids, alkaloids, and proteins, have been isolated from higher plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…WMV is one of the economically important plant viruses in the world and has a wide range of hosts, including at least 170 plant species from 27 plant families. WMV can infect all tissues and causes adverse effects in cucurbits [6]. Our investigation about field disease revealed that a majority of C. pepo L. exhibited typical mosaic symptoms in Shanxi, which seriously affected their yield and quality.…”
Section: Introductionmentioning
confidence: 87%
“…The literature includes a large number of studies focusing on the use of essential oils and crude plant extracts in the control of several types of pests, with favorable results. Pesticide-like chemical species found in plants have been reported to be effective against insects [ 121 ], fungi [ 122 ], bacteria [ 123 ], nematodes [ 124 ], and viruses [ 125 ]. Thus, the insecticidal effect of Artemisia annua , A. absinthium , A. camphorata , A. dracunculus , and A. vulgaris was investigated on the larvae of the watermelon worm, Diaphania hyalinata (Lepidoptera: Crambidae), a pest of Cucurbitaceae , as well as for their selectivity to ants of the species Solenopsis saevissima (Smith) (Hymenoptera: Formicidae) and the jatai bee, Tetragonisca angustula (Latreille) (Meliponinae).…”
Section: Biopesticides: Alternatives To Synthetic Pesticides and Thei...mentioning
confidence: 99%